Pediatric Nephrology - Avner, Ellis D.; Harmon, William E.; Niaudet, Patrick; Yoshikawa, Norishige; Emma, Francesco; Goldstein, Stuart L. (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This new edition of Pediatric Nephrology, now in three volumes, has been extensively updated and also contains much new material. Its organization flows logically from renal physiology to clinical evaluation. Discussion of the development of kidney structure and function is followed by sections on basic and translational research and on clinical methods, including laboratory tests, diagnostic imaging, and renal pathology. Comprehensive chapters then cover each of the childhood kidney diseases, grouped according to major disease categories. All of these chapters make new genetic information easily understandable for the practitioner and use many algorithms and diagrams to describe appropriate clinical evaluation of symptoms, differential diagnosis, specific diagnostics, and currently available therapies. Over the course of the previous six editions, Pediatric Nephrology has become the standard reference text for students, trainees, and practicing physicians (pediatricians, nephrologists, internists, and urologists), subspecialists, and allied health professionals seeking information about children's kidney diseases. It is global in perspective, reflecting the fact that the international group of editors are all acknowledged world experts. This book serves as a superb reference and is an invaluable asset during clinical encounters with children having all forms of kidney disease.